KUALITAS HIDUP DAN PERTUMBUHAN EKONOMI, STUDI KASUS DKI JAKARTA DAN DAERAH PENYANGGANYA - Karim, Malik Al; Utomo, Galih Jati; Fauziah, Bella (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
This study aims to analyze the phenomenon of urban sprawl development from aspects of value added, quality of life and economic growth to sub urban area of DKI Jakarta. The city are Bekasi City, Bekasi Regency, Depok City, Bogor City, Bogor Regency, Tangerang City, South Tangerang City, and Tangerang Regency. The research method was desk study with Â variables population, typology of city, Human Development Index (HDI), Gross Regional Domestic Product (GRDP), education level, proportion of labor, access to Jakarta and distribution of settlements. The results of this research are (1) urban sprawl increases the population and the development of regions around the city including economic agglomeration to the sub urban area. It can be seen from the change of land use in each region become an area of settlement, commercial, industrial, or service and the development of new infrastructure and centers of economic growth. Â (2) economic growth in the sub urban area have an increase in GDP per year. Based on this, there is no competitiveness between the DKI Jakarta sub urban areas developing not based on competition but complementary. (3) The city of South Tangerang is considered to have the best quality of life. This is seen from the highest value of South Tangerang City HDI compared to other regions.Â